A LATE MIOCENE ARGYROLAGIDAE (MAMMALIA, METATHERIA, BONAPARTHERIIFORMES) FROM NORTHWESTERN ARGENTINA (Ameghiniana, 2015)
In this contribution we present the first record of a member of the family Argyrolagidae (Metatheria) recovered from the India Muerta Formation (late Miocene) exposed near San Miguel de Tucumán, Tucumán Province, Argentina. The specimen is represented by a fragment of right maxilla with M1 –4 and is referred here as Microtragulus Ameghino. It clearly differs from other members of the genus that preserve the upper dentition. Nevertheless, the impossibility of comparing this material with species only known by lower dentition, such as Microtragulus catamarcensis (Kraglievich) prevent us from establishing whether this is a new species or not. The comparisons performed allow us to identify characters from the upper dentition differing between Microtragulus and Argyrolagus Ameghino. These characters, in turn, led to the reassignment of a species previously assigned to Microtragulus. The new record reported here, the third known of Microtragulus from northwestern Argentina, broadens the geographic range of the genus, known from the Atlantic coast of Argentina and several localities of the Andean highlands and the foothills of the cordilleran range.Resumen. UN ARGYROLAGIDAE (MAMMALIA, METATHERIA, BONAPARTHERIIFORMES) DEL MIOCENO TARDÍO DE LA PROVINCIA DE TUCUMÁN, ARGENTINA. En esta contribución se reporta el primer registro de un ejemplar de la familia Argyrolagidae (Metatheria) para la provincia de Tucumán, Argentina. El espécimen corresponde a un fragmento maxilar derecho con los M1–4 y proviene de sedimentos de la Formación India Muerta (Mioceno tardío) expuestos en las cercanías de la ciudad de San Miguel de Tucumán. Los rasgos dentarios permiten referir este material al género Microtragulus Ameghino. Si bien difiere claramente de las especies del género con las cuales puede ser comparado directamente, la imposibilidad de compararlo con Microtragulus catamarcensis (Kraglievich), proveniente de la Formación Andalhuala (Catamarca) impide establecer si se trata de un nuevo taxón. Por otra parte, la comparación entre éste y otros argirolágidos neógenos sirvió para identificar rasgos propios de la dentición superior que diferencian a los géneros Argyrolagus Ameghino y Microtragulus y que permitieron revisar la asignación de algunas especies. Este registro representa el tercer reporte de Microtragulus para el noroeste argentino y amplía el rango geográfico del género, que se distribuye tanto en localidades de la costa atlántica como en zonas de altura y aledañas a la franja andina de América del Sur.